2021
DOI: 10.1021/jacs.0c12568
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorescence-Detected Coordination-Induced Spin State Switch

Abstract: The response of the spin state to in situ variation of the coordination number (CISSS) is a promising and viable approach to smart sensor materials, yet it suffers to date from insensitive detection. Herein, we present the synthetic access to a family of planar nickel(II) complexes, whose CISSS is sensitively followed by means of fluorescence detection. For this purpose, nickel(II) complexes with four phenazine-based Schiff base-like ligands were synthesized and characterized through solution-phase spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 61 publications
3
60
1
Order By: Relevance
“…28 We found excellent agreement of predicted and experimental metrics across the entire reference set (error in bond lengths <2 pm). Taken together with the general close compliance between model and experiment of planar d 8 configured complexes, [36][37][38][39] As could be concluded from strictly diamagnetic behaviour of the complexes in the 1 H NMR spectra, all complexes exhibit close-to-ideal square planar coordination of the S^N^N^O donor set. The bond length of the coordinated C-S moiety cluster at 1.78 ± 0.01 Å, indicating dominant ene-thiolate character.…”
Section: Synthesis Of the Complexessupporting
confidence: 76%
See 1 more Smart Citation
“…28 We found excellent agreement of predicted and experimental metrics across the entire reference set (error in bond lengths <2 pm). Taken together with the general close compliance between model and experiment of planar d 8 configured complexes, [36][37][38][39] As could be concluded from strictly diamagnetic behaviour of the complexes in the 1 H NMR spectra, all complexes exhibit close-to-ideal square planar coordination of the S^N^N^O donor set. The bond length of the coordinated C-S moiety cluster at 1.78 ± 0.01 Å, indicating dominant ene-thiolate character.…”
Section: Synthesis Of the Complexessupporting
confidence: 76%
“…These settings gave excellent agreement with experiment in several previous studies on square-planar d 8 -based systems. [37][38][39] In keeping with this, the experimental transition energy and intensity could be satisfyingly matched for all complexes in this study (cf., Fig. 4 for Ni; for more spectra see Fig.…”
Section: Dalton Transactionssupporting
confidence: 59%
“…Recently reported DFT and TD-DFT calculations on the molecular and electronic structures of planar d 8 configured Ni II , Pd II , and Pt II complexes have shown that the reliability of calculated data with experimental data [58][59][60][61][62][63][64][65][66] is very much dependent on functionals and basis sets. Furthermore, comparative DFT and experimental studies for these three metals were recently reported [62][63][64][65][66][67] allowing to gauge for the differences of these three metals.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, enhanced affinity for Lewisbases has been recently reported for nickel(II) complexes of CF3-decorated ligands. [20] [Zn( 1…”
Section: Speciation-dependent Emission Propertiesmentioning
confidence: 99%